Overlapping structural and functional connectivity disruptions in clinical high-risk for psychosis participants: A network analysis study - Angus Paton; Tineke Grent- ’t-Jong; Ruchika Gajwani; Joachim Gross; Andrew I. Gumley; Stephen M. Lawrie; Matthias Schwannauer; Frauke Schultze-Lutter; Peter J. Uhlhaas (NeuroImage: Clinical)
Schizophrenia involves aberrant connectivity of anatomical and functional networks. However, it is currently unclear whether such disruptions are present in clinical high-risk for psychosis (CHR-P) participants and whether there may be an overlap between structural and functional connectivity alterations.We obtained diffusion magnetic resonance imaging (dMRI) and resting-state, magnetic resonance imaging (rsfMRI) data from N = 110 CHR-P participants and N = 49 healthy controls (HC). A network analysis approach was employed to explore differences in dMRI and rsfMRI connectivity as well as potential overlap between both modalities. In addition, correlations between dMRI and rsfMRI-data, clinical and neurocognitive variables as well as with clinical outcomes were investigated.We observed hyper- and hypoconnectivity across occipital, parietal, temporal, and frontal cortices in both dMRI and rsfMRI-data in CHR-Ps. Moreover, dMRI- and rsfMRI-defined overlapping nodes that differed between CHR-Ps vs. HC overlapped with visual networks, right ventral attention network, and right default mode network. Correlational analyses indicated significant relationships between the severity of CHR-P symptoms, cognitive deficits, and dMRI/rsfMRI-defined hypo- and hyper-connectivity. Finally, CHR-P individuals with persistent attenuated psychotic symptoms (APS) were characterised by aberrant dMRI and rsfMRI connectivity compared to non-persistent APS.Our study shows subtle but widespread disruptions in dMRI and rsfMRI connectivity in CHR-P participants. Specifically, we identified several occipital, parietal, temporal, and frontal regions that were characterised by hyper and hypoconnectivity which correlated with the severity of clinical symptoms and cognitive impairments. Moreover, our findings suggest that dMRI and rsfMRI connectivity measures could serve as a potential biomarker for clinical outcomes in CHR-Ps.